APLIKASI METODE TREN WAKTU SATU RAGAM DALAM PERAMALAN TOLERANSI KOMODITAS PANGAN TERHADAP PERUBAHAN IKLIM DI PAPUA - Garuda, Sitti Raodah; Baliadi, Yuliantoro (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2018)
Climate change has an impact on decreasing agricultural production, especially food crops. The rate of decline in agricultural production due to climate change ranges from 5-20%.The objective of this study was to forecastfood-cropsat Papua Province that are tolerance and adaptable to climate change using trend method. This study used four models of trend analysis, i.e: linear least square pattern, quadratic, exponential, and moving averages, with secondary data base of rice, maize, soybean and sweet potato production; climate data (rainfall); productivity and harvested areas from 1970-2015. These data were used to estimate food crop production in the year of climate change to determine their impact on food-crop production. Results showed that soybean was the most sensitive crop to climate change. It has the biggest impact on production, yield declined on both El Nino (10.7%) and La Nina (11.4%). The lowest impact was on rice crop, which is generally cultivated on the wetlands, El Nino decreased of production of 2.9% and La Nina increased production 2.4%, respectively. Two other crops, maize production decreased 7.4% on the El Nino and 3.9% increased during the La Nina. Futhermore, the the analysis revealed that sweet potatois the most resistant crop to climate change since it production increase by 2.5% during El Nino. As conclusion, moving average trendof order 2 model was most appropriate to estimate the value of rice and soybean production in the 1970-2015 period.The quadratictrend model wasapropriateÂ to estimate maize and sweet potato production based on its the MAPE, MAD, and MSD values.